Scope of legal liability for damages caused by artificial intelligence machines - SNOUCI, Ali; BELFEDEL, Mohamed (Journal of Human Sciences, 2025)
The legal liability of AI machines explores the ways of developing and deploying AI from a legal perspective. Using AI in a safe, reliable and ethical manner would bring transparency and help resolve many legal issues. The problem lies in determining the scope of legal liability for damages caused by AI machines; by adopting an analytical and descriptive approach, to enable the legislator to create a legal framework to address the challenges arising from the use of AI. In this paper, we discuss the nature of AI and its components in the first section, and the legal liability arising from the actions of AI in the second section. Let us conclude that a robot is nothing without programs. Recognizing the legal personality of a robot could have serious consequences. Traditional liability provisions are not sufficient with the emergence of new generations of AI capable of thinking, learning and making decisions independently.